New type of difference sequence spaces of fuzzy real numbers - Tripathy, Binod Chandra; Baruah, Achyutanada (Mathematical Modelling and Analysis, 2009)
In this paper we introduce the natation difference operator Δrn(m ≥ 0, an integer) for studying properties of some sequence spaces. We define the sequence spaces l ∞ F (Δm), cF(Δm), cF o(Δm) and investigate their properties like solid‐ness, convergence free, symmetricity, completeness.First published online: 14 Oct 2010